Oe3r Strategy Implementation as an Innovation on Inquiry Based Learning toward Redox Reaction Mastery - Imas, Ahmad Fariq; Sutrisno, Sutrisno; Widarti, Hayuni Retno Widarti Retno (Universitas Negeri Malang, 2019)
The Oe3r strategy is an effort to develop a learning model based on inquiry. Oe3r strategy consists of orientation, exploration, explanation, elaboration, and reflection. This study aims to describe the implementation of the Oe3r strategy on the chapter redox reaction and obtain student responses on it. The research used a quantitative descriptive method. Implementation description is derived from observations on the learning process, while student responses are obtained by capturing responses through questionnaires. The implementation of the Oe3r strategy was carried out in High school students with 35 students. The results of this research indicate that students give good to respond, felling meaningful on the learning process and expect the Oe3r strategy can be applied in other chapters.